Wood Preservatives - Frederick M. Fishel (EDIS)
This 6-page document describes the purpose of applying preservatives to various wood products. A description of wood preservatives registered for use in Florida is also provided. Written by Frederick M. Fishel and published by the UF/IFAS Agronomy Department, July 2018. https://edis.ifas.ufl.edu/pi276